2015
DOI: 10.7860/jcdr/2015/14079.6554
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Transcerebellar Diameter/ Abdominal Circumference Versus Head Circumference/Abdominal Circumference in Predicting Asymmetric Intrauterine Growth Retardation

Abstract: Background: The high incidence of IUGR and its low recognition lead to increasing perinatal morbidity and mortality for which prediction of IUGR with timely management decisions is of paramount importance. Many studies have compared the efficacy of several gestational age independent parameters and found that TCD/AC is a better predictor of asymmetric IUGR. Aim:To compare the accuracy of transcerebellar diameter/ abdominal circumference with head circumference/abdominal circumference in predicting asymmetric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…Consequently, although the TCD/AC ratio increased slightly as GA increased, this rise was negligible, indicating that the ratio would remain constant regardless of GA. Comparable results were found in the studies that were carried out by Srividya et al and Bhimarao et al [12,15]. In the research carried out by Bhimarao et al, it was found that there was an insignificant association between TCD/AC and GA (r2=0.13, p>0.05) after 20 weeks of gestation [15].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Consequently, although the TCD/AC ratio increased slightly as GA increased, this rise was negligible, indicating that the ratio would remain constant regardless of GA. Comparable results were found in the studies that were carried out by Srividya et al and Bhimarao et al [12,15]. In the research carried out by Bhimarao et al, it was found that there was an insignificant association between TCD/AC and GA (r2=0.13, p>0.05) after 20 weeks of gestation [15].…”
Section: Discussionmentioning
confidence: 61%
“…Comparable results were found in the studies that were carried out by Srividya et al and Bhimarao et al [12,15]. In the research carried out by Bhimarao et al, it was found that there was an insignificant association between TCD/AC and GA (r2=0.13, p>0.05) after 20 weeks of gestation [15].…”
Section: Discussionmentioning
confidence: 61%
“…Por lo tanto, su crecimiento está menos afectado por la restricción del crecimiento fetal. Estas características hacen que el DTC sea uno de los parámetros ecográficos más fiables para establecer la EG (6,13,15) . Además, puede ser un parámetro útil en determinadas circunstancias, como presentación de nalgas y dolicocefalia (excepto en la anencefalia), en las que otros parámetros biométricos no son útiles (16) .…”
Section: Discussionunclassified
“…Existe evidencia que el cerebelo fetal presenta crecimiento progresivo a lo largo del embarazo (5) . Además, tanto el cerebro como el cerebelo están menos afectados por la restricción del crecimiento intrauterino fetal secundario a insuficiencia placentaria, lo que sugiere un mecanismo de preservación del crecimiento cerebeloso (6,7) . El diámetro transversal del cerebelo (DTC) es un estimador único y fiable de la EG al final del embarazo (8) .…”
unclassified
“…In the ultrasound literature, the transcerebellar diameter (TCD) is well-established as a valid metric for determining GA. Because the posterior fossa is not impacted by external pressure such as fetal malposition, breech presentation, or oligohydrammnios, which may result in distortion of the fetal head, TCD may be a more accurate predictor than BPD. When femur length is unsatisfactory due to femoral achondroplasia, the TCD might be utilized instead (4).…”
Section: Introductionmentioning
confidence: 99%